Impacts of plasma-induced damage due to UV light irradiation during etching on Ge fin fabrication and device performance of Ge fin field-effect transistors. (11th January 2017) - Mizubayashi, Wataru; Noda, Shuichi; Ishikawa, Yuki; Nishi, Takashi; Kikuchi, Akio; Ota, Hiroyuki; Su, Ping-Hsun; Li, Yiming; Samukawa, Seiji; Endo, Kazuhiko
Abstract: We investigated the impacts of plasma-induced damage due to UV light irradiation during etching on Ge fin fabrication and the device performance of Ge fin field-effect transistors (Ge FinFETs). UV light irradiation during etching affected the shape of the Ge fin and the surface roughness of the Ge fin sidewall. A vertical and smooth Ge fin could be fabricated by neutral beam etching without UV light irradiation. The performances of Ge FinFETs fabricated by neutral beam etching were markedly improved as compared to those of Ge FinFETs fabricated by inductively coupled plasma etching, in which the UV light has an impact.